Authorial visibility in the introduction and post-methodology sections of research papers from different disciplines - del Saz Rubio,Ma Milagros (Pontificia Universidad Católica de Valparaíso. Instituto de Literatura y Ciencias del Lenguaje, 2021)
Abstract Recent studies have shown that academic writing is not completely impersonal. Rather, the writers’ presence is part and parcel of academic prose as authors need to portray a convincing authorial voice, while also being able to tentatively present their claims and findings (Hyland 2001a; 2002b). One of the rhetorical strategies at the researchers’ disposal is the use of personal pronouns and their corresponding determiners (Tang & John, 1999; Martínez, 2005; Mur-Dueñas, 2007). With this in mind, a corpus of 30 research papers from the disciplines of engineering, medicine and linguistics will be examined in order to first assess the traces of authorial presence through the use of personal pronouns, and their corresponding determiners, or noun phrases such as ‘the authors’, ‘the researchers’, together with their function across the introduction and the sections which report findings and/or discuss them. Findings show significant differences from a statistical point of view in both the way and frequency with which authors from each discipline make themselves visible in the different sections under analysis. While all disciplines show a preference for the use of explicit authorial devices, engineering relies more on other indirect or implicit ways of author presentation. Medicine, on its part, is the discipline which employs more authorial devices per 1,000 words in spite of the fact that its articles are shorter, and its sections are much less rhetorically complex if compared to those of Linguistics and Engineering.